Radiological Characteristics of Patients With Anti-MDA5–Antibody-Positive Dermatomyositis in 18F-FDG PET/CT: A Pilot Study - Cao, Heng; Liang, Junyu; Xu, Danyi; Liu, Yinuo; Yao, Yinan; Sun, Yiduo; He, Ye; Lin, Jin (Frontiers in Medicine, 2021)
Objective. To elucidate the 18F-Fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) characteristics and its prognostic value in anti-melanoma differentiation associated protein 5 antibody positive (anti-MDA5+) dermatomyositis (DM) patients. Methods. This retrospective cross-sectional study included 26 anti-MDA5+ DM patients and 43 anti-MDA5 negative (anti-MDA5-) idiopathic inflammatory myopathy (IIM) patients who were examined by 18F-FDG PET/CT from January 1st 2017 to December 31st 2020. The maximum standardized uptake value (SUVmax) of multiple organs and other clinical characteristics of patients were measured and analyzed. Results. Compared with the anti-MDA5- group, patients in the anti-MDA5+ group showed higher bilateral lung SUVmax (p=0.029), higher SUVmax of spleen (p=0.011) and bone marrow (p=0.048). Significant correlations between the spleen SUVmax and serum ferritin levels (r = 0.398, p <0.001), ESR (r = 0.274, p= 0.023), platelet count (r= − 0.265, p= 0.028), myositis disease activity assessment score (r = 0.332, p = 0.005), bone marrow SUVmax (r=0.564, p<0.001) and bilateral lung SUVmax (r=0.393, p<0.001) were as well observed. Conclusion. 18F-FDG PET/CT was found valuable in quantifying the pulmonary focal inflammation and potentially unveil the distinctive characteristics and pathophysiological mechanisms in anti-MDA5+ DM patients.